Mallard duck (Anas platyrhynchos)‐mediated dispersal of Lemnaceae: a contributing factor in the spread of invasive Lemna minuta?. (6th May 2014) - Coughlan, N. E.; Kelly, T. C.; Jansen, M. A. K.
Abstract: Our ability to predict and manage the spread of alien, invasive plants is limited by a lack of understanding of dispersal potential. Invasive Lemna minuta has spread within a few decennia throughout Europe. However, the mechanism by which the species continues to spread remains a matter of speculation. In this study, hypothesised epizoochorous transport of L. minuta propagules by mallard ducks was investigated. Landolt (Biosystematic investigations in the family of duckweeds (Lemnaceae) (Vol. 2), The family of Lemnaceae – a monographic study (Vol. 1), 1986, Veröffentlichungen des Geobotanischen Institutes Der Eidg. Techniasche Hochschule, Stiftung Rübel, Zürich, Switzerland) referred to desiccation as the key limitation of the "colonization capability" of Lemnaceae. Therefore, we analysed retention of viability in L. minuta kept outside the liquid growth medium. Our data show prolonged viability of L. minuta fronds inserted between the feathers of a mallard duck. Consistently, the relative humidity between feathers ranged between 65% and 90%. Taking together evidence of entanglement and retention of L. minuta between the feathers of live ducks, with retention of viability, we consider it likely that mallards contribute to L. minuta dispersal. These data have implications for the management strategy of this invasive species.